1992
DOI: 10.1002/qua.560420433
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of poly(pyrrole–thiophene) copolymers: Design of polymeric quasi‐one‐dimensional superlattices

Abstract: Ab initio band structure results of polypyrrole (PPY) and polythiophene (PTP) obtained with a double-zeta basis set are reported. The electronic density of states (ws) of the various quasione-dimensional copolymers (superlattices) of the type (A,B.h, ( A = pyrrole; B = thiophene) have been calculated numerically within the ab initio SCF tight-binding approximation. These copolymers on the basis of the band positions of PPY and PTP are found to belong to the class of type I1 (staggered) superlattices. The trend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…In this way it should be possible to reach theoretical predictions about useful candidates for synthetic metals. Important ab initio investigations on the search for low-gap polymers (in different directions regarding the chemical structure) were reported by Bakshi et al [46][47][48][49][50][51]. For a comprehensive review of the large amount of work performed by the group of Ladik on this topic see [52].…”
Section: Introductionmentioning
confidence: 99%
“…In this way it should be possible to reach theoretical predictions about useful candidates for synthetic metals. Important ab initio investigations on the search for low-gap polymers (in different directions regarding the chemical structure) were reported by Bakshi et al [46][47][48][49][50][51]. For a comprehensive review of the large amount of work performed by the group of Ladik on this topic see [52].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the electronic states of heterostructures similar to these have been reported by other authors, employing conventional quantum-chemical or solid-state methods. [39][40][41][42][43][44]…”
Section: Model Heterostructuresmentioning
confidence: 99%
“…Studies of the electronic states of heterostructures similar to these have been reported by other authors, employing conventional quantum-chemical or solid-state methods. [39][40][41][42][43][44] IV. COMPUTATIONAL IMPLEMENTATION A practical implementation of the EMO theory requires four input parameters for each parent polymer: the HOCO and LUCO energies and the hole and electron effective masses.…”
Section: Model Heterostructuresmentioning
confidence: 99%
“…Quantum-chemical calculations have been carried out for oligothiophenes 13,14 and for copolymers based on pyrrole and thiophene units 15 in order to understand the properties of the respective polymers in neutral and doped states. It is worth mentioning that only oligomers with anti chains ͓Fig.…”
Section: Introductionmentioning
confidence: 99%